Ri-velare l'orrore. Ricorsività del thermal imaging nel cinema bellico contemporaneo (Materiali di Estetica. Terza serie, 2024)
Thermal imaging, a product of image processing techniques that visualize the thermal energy emitted by objects, bodies and life forms, has gained prominence in today's post-optical visual culture. Its application in various operative fields and for diverse purposes has made it a significant element in contemporary war imagery. Cinema, in particular, has been quick to incorporate thermal imaging into its documentary and fictional productions. Through an analysis of recent war films, this paper aims to shed light on the unique perspective that thermal imaging offers especially in its military use, focusing on the striking transformation of the enemy's body and how war horror is translated into visual forms.
Keywords: horror; body; contemporary cinema,; war imagery; thermal imaging